The Emergence of Multicultural Characteristics in Virtual Team - Karim, Daniel; Gustomo, Aurik; Wisesa, Anggara (Fakultas Ekonomi dan Bisnis, Telkom University., 2023)
The advancement of information and communication technology grant access for businesses to reach global workforce. In a condition where companies hire their employee from cross-border market, the exposure of multicultural differences will be more in contact. Some of the problem faced by virtual multicultural team are cultural discrepancy, communication problem, long distance conflict, and lack of synergy. The objective of this study is to explore the multicultural characteristics emerged from virtual team activity to minimize the problem. This research adopts a case study to examine the comprehensive understanding of virtual multicultural team activity and get new insight from dwelling activity into the context directly. This study has two results: a virtual team and multicultural team characteristics in digital company and Hybrid company. This study can help practitioners identify what multicultural level of focus is well-suited to their current business model and give researcher an overview of future research on the alternatives in managing virtual multicultural team by building virtual multicultural team framework. Keywords — Multicultural; Virtual Team, Hybrid Company, Digital Company